Construction of Overexpression Vector with TYR7523 Gene and Its Effect on Browning in Macrocybe gigantea - Jinyun Gao; Shuqing Song; Xinqian Liu; Zhuanlin Mo; Meihua Mo (Journal of Fungi)
Macrocybe gigantea is a rare high-temperature edible fungus known for its resistance to browning. Previous studies suggested that the anti-browning property of the SCAU4 strain might be associated with low expression levels of the TYR7523 gene. In this study, an overexpression vector for the TYR7523 gene was constructed and introduced into SCAU4 mycelium using an Agrobacterium-mediated transformation method. After three rounds of hygromycin resistance screening, successful transformants were identified through PCR amplification and validated by qRT-PCR analysis, confirming a 3.47-fold upregulation of TYR7523 expression. The overexpression strain OE7523 was compared with the wild-type SCAU4 strain in terms of growth rate, browning degree, and tyrosinase activity. Although there was no significant difference in growth rate on the mother culture medium, OE7523 showed faster growth on the stock culture and mycelium culture medium. In the late storage period, OE7523 exhibited a higher browning degree and tyrosinase activity than SCAU4, suggesting a potential role of TYR7523 in fruiting body browning. Physiological analyses indicated that low TYR7523 expression may contribute to storage tolerance, while high expression influenced postharvest browning and preservation duration. The results provide data support for further study on the function of TYR7523 gene of Macrocybe gigantea.